Pathways to Enable Primary Healthcare Nurses in Providing Comprehensive Primary Healthcare to Rural, Tribal Communities in Rajasthan, India - Amin, Arpita; Dutta, Manisha; Brahmawar Mohan, Sanjana; Mohan, Pavitra (Frontiers in Public Health, 2020)
Background: Emerging health needs and uneven distribution of human resources of health have led to poor access to quality healthcare in rural areas. Rural pathways provide an approach to plan and evaluate strategies for ensuring availability, retention, motivation and performance of human resources for health in rural areas. While effectiveness of primary healthcare (PHC) nurses to deliver primary health care is established, there is not enough evidence on ways to ensure their availability, retention, motivation and performance. The paper draws on the program experience, evidence from a primary healthcare network (AMRIT Clinics), in which nurses play a central role in delivering primary healthcare in rural tribal areas of Rajasthan, India, to bridge this gap. Methods: Rural, tribal areas of Rajasthan have limited access to functional healthcare facilities, despite having a high burden of diseases. We used the rural pathway approach to describe factors that contributed to the performance of nurses in AMRIT Clinics. We analysed information from human resource information system and health management information system; and supplemented it with semi-structured interviews with nurses, conducted by an independent organization. Results: Most nurses were sourced from rural and tribal communities that the clinics serve; nurses from these communities were likely to have a higher retention than those from urban areas. Sourcing from rural and tribal communities, on-going training in clinical and social skills, a non-hierarchical work environment and individualized mentoring appear to be responsible for high motivation of the primary healthcare nurses in AMRIT Clinics. Task redistribution with due credentialing, intensive and on-going training and access to teleconsultation helped in sustaining high performance. However, family expectations to perform gendered roles and pull of government jobs affect their retention. Conclusion: Rural and remote areas with healthcare needs and scarcity of health provisions need to optimize the health workforce by adopting a multi-pronged pathway in its design and implementation. At the same time, there is need to focus on structural factors that affect retention of workforce within the pathway. Our experience highlights pathway of upskilling PHC nurses in providing comprehensive primary healthcare in rural and remote communities in Low and Middle-Income Countries (LMICs).